The clinical effects of the venomous Lessepsian migrant fish Plotosus lineatus (Thunberg, 1787) in the Southeastern Mediterranean Sea. (4th May 2018) - Bentur, Yedidia; Altunin, Sergey; Levdov, Iris; Golani, Daniel; Spanier, Ehud; Edelist, Dor; Lurie, Yael
Abstract: Context: Plotosus lineatus is a venomous fish that has migrated from the Indo-Pacific region to the Mediterranean Sea (Lessepsian migrant). Its presence in the Mediterranean Sea was first recorded in 2002 and was observed in growing schools. Its spines contain toxins with lytic, hemolytic and edematous activities. Objective: To characterize the injuries caused by Plotosus lineatus in the Southeastern Mediterranean Sea. Methods: A prospective observational case series of consultations provided by a national Poison Center pertaining to Plotosus lineatus from 2007 to 2016. Demographic and clinical data and method of fish identification were retrieved from the medical toxicological records, and described. Results: Eighty four cases were included; the main findings are: median age 35 (range 3–80) years, 91.7% males, 51.2% fishermen, 78.6% palm injuries, 94% and 4.8% were mildly and moderately injured, respectively. Main local manifestations included pain, puncture wound, swelling, and erythema (90.5%, 70.2%, 33.3%, and 16.7%, respectively). Systemic signs were minor and infrequent (≤7.1%), including hypertension, tachycardia, vomiting, chills, and weakness. Management included wound disinfection, immersion in hot water, tetanus prophylaxis, and analgesics. No patient required hospital admission. The fish was identified mostly by the victim with the aid of the Poison Center (mainly by typical description, and a picture), and some by marine biologists. Conclusions: Plotosus lineatus is a new fish in the Southeastern Mediterranean Sea. It affects fishermen handling fishing nets, and beach hikers stepping on or holding it. Injuries caused by its spines usually result in minor effects; pain may be intense. Treatment includes disinfection, analgesics, and antitetanus and antibiotics as needed. No lethal cases were recorded, unlike exposure of animals to the venom of the Indo-Pacific species; reason is unclear. Our series illustrates the consequences of manmade disruption of ecosystem resulting in invasion of toxic species to a new environment, affecting human health.